Coal Contractor Mining Facts - 2001 (The National Institute for Occupational Safety and Health (NIOSH), 2003)
1. The Federal Mine Safety and Health Act of 1977 defines an independent contractor as "any person, partnership, corporation, subsidiary of a corporation, firm, association or other organization that contracts to perform services or construction at a mine." Contractors that perform specific types of work (e.g., shaft and slope sinking, material handling within mine property, drilling and blasting) are required to report the number of employees who perform work at coal mines and at metal and nonmetal mines.